(3QSGdI GdbGUYI ddaQYhf GdOYi GdaGVMIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi GdehddG GdefRI Yf JMOJO GdaGSbjf hGdeGQbjf hJhSdJ Edjg HYHOg GdbGFe GdgdGc ef Tc ajg s
(3BNQgG (B:s
(3hegdc ef Tc ai XghQg HGdEfJbGe HSja ehdGfG ef GdeQbI GdLGMOjf GdeTQcjf hGdeJcHQjf JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B64s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds